Pengembangan Augmented Reality Sebagai Media Pembelajaran Alat Musik Ritmis dan Melodis Tradisional Indonesia untuk Siswa Sekolah Dasar Menggunakan Metode MDLC - Ni Komang Metri Malia Aiswarya; Ni Wayan Marti; I Ketut Purnamawan (TIN: Terapan Informatika Nusantara, 2026)
Music Arts learning at SD Negeri 5 Banyuning remains conventional, relying on textbooks and singing activities without the support of interactive learning media, causing students to experience difficulties in understanding and recognizing traditional Indonesian musical instruments. This study aims to design and implement Augmented Reality-based learning media as a supporting tool for Music Arts learning for students at SD Negeri 5 Banyuning. The method used is the Multimedia Development Life Cycle, which consists of the concept, design, material collecting, assembly, testing, and distribution stages. The developed media is capable of displaying three-dimensional objects of traditional Indonesian rhythmic and melodic musical instruments along with descriptive information and original audio sounds of the instruments through marker scanning. Testing was conducted through content expert review, media expert review, and user response testing. Data analysis for the user response test used the System Usability Scale method. The research respondents consisted of 27 Grade IV students and 3 teachers, bringing the total number of respondents to 30 individuals. The results of the content expert review showed a validity index score of 1.0, categorized as highly valid, while the media expert review yielded a validity index score of 0.9, also categorized as highly valid. Meanwhile, the user response test obtained an average System Usability Scale score of 80.43, categorized as excellent. The findings indicate that Augmented Reality-based learning media demonstrates a very high level of usability, is easy to use, and is suitable for use as supporting media for Music Arts learning on the topic of traditional Indonesian rhythmic and melodic musical instruments. This study contributes to the development of Augmented Reality-based learning media as an innovative solution to improve the quality of music arts learning through a more interactive, visual, and contextual presentation of traditional Indonesian rhythmic and melodic musical instruments, thereby encouraging active student engagement in the learning process.